Contrast Radiographic Technique for Pervious Urachus in a Jersey Calf - S.Kokila; N.Krishnaveni (The Indian Veterinary Journal, 2023)
Pervious urachus refers to a spectrum of umbilical disorders that result from the failure of the involution of normal embryologic tissues that connect the developing bladder to the umbilical cord. A 20 days old female Jersey calf was presented to VCC, VCRI, Tirunelveli with the history of dribbling urine from the ventral abdomen (umbilicus) and also through the urethral orifice. Plain and contrast radiography using Iohexol of the abdomen was evaluated. The case was confirmed as congenital Pervious urachus. The urachus was accessed by midventral skin incision and double ligated. Animal started urinating through the urethral opening on the same.